Of forests and grasslands: human, primate, and ungulate palaeoecology in Late Pleistocene-Holocene Sri Lanka - Amano, Noel; Wedage, Oshan; Ilgner, Jana; Boivin, Nicole; Petraglia, Michael; Roberts, Patrick (Frontiers in Earth Science, 2023)
The Wet Zone region of Sri Lanka has provided some of the earliest direct evidence of human utilization of rainforest resources anywhere in the world. Stable isotope analysis of human and animal remains, alongside detailed zooarchaeological analyses, have demonstrated reliance on rainforest resources as far back as 48,000 years ago. However, changes in human adaptations and the varying niches of exploited fauna, through major climatic periods such as the Terminal Pleistocene and Holocene transition, remain relatively under-explored. Here, we present the results of stable carbon (δ13C) and oxygen (δ18O) isotope analyses of dental enamel from 311 animal and eight human teeth recovered from recent excavations at Fa-Hien Lena and Kitulgala Beli-lena from contexts spanning the Late Pleistocene and Holocene. Our data for human teeth from the Terminal Pleistocene and Holocene layers of Fa-Hien Lena and the Holocene layers of Kitulgala Beli-lena show little departure from rainforest resource reliance between the Pleistocene and Holocene. Meanwhile, the most dominant faunal taxa, including cercopithecid monkeys, show a similar stability in canopied forest habitation across the different species. However, δ13C data from ungulates found at Fa-Hien Lena indicate human populations did have access to forest edge and grassland habitats, suggesting either specific foraging trips or long-distance trade with other communities. In addition, our reporting of an Early Holocene presence of rhinoceros in the Wet Zone forest of Sri Lanka, the last fossil occurrence of this now regionally-extirpated taxon, highlights ongoing human interactions with large mammal communities on the island. We argue that our data demonstrate the benefits of detailed isotopic and zooarchaeological studies for detailed insights into the nature of tropical human adaptations through time.